Acquisition of third person personal pronouns by L1 Malay speakers - Soo, Carolyn Kum Yoke; Wong, Bee Eng (Universiti Putra Malaysia Press, 2012)
This study investigates the acquisition of English third personal person pronouns (henceforth third person pronouns) by first language (L1) Malay learners. The theoretical framework adopted for the study is the Failed Functional Features Hypothesis (FFFH) (Hawkins & Chan, 1997) which claims that second language (L2) learners who begin the task after a particular period of time will not be able to acquire the L2 property and its associated functional features if these have not been instantiated in the learners’ L1. Specifically the aim of this study is to find out to what extent the learners of three different age groups and matched levels of proficiency are able to acquire the English third person pronouns and their associated features (gender, case and number). One hundred and fifty (50 elementary, 50 intermediate, 50 advanced) L1 Malay speakers participated in the study. Two instruments, the Oxford Placement Test (OPT) and a Grammaticality Judgment Task (GJT), were administered to the respondents. The OPT was used to determine the proficiency level of the respondents. The main task, i.e. the GJT, comprised 72 items (both grammatical and ungrammatical) on third person pronouns, tests the respondents’ knowledge on gender, case and number. The data obtained indicated that the learners in the elementary group had the most difficulty in the acquisition of the items tested, followed by the intermediate and the advanced groups, respectively. This indicates that the learners go through developmental stages of acquisition. Overall, the learners’ performances for the grammatical items were better than the ungrammatical items even at the advanced level, implying that at ultimate attainment, they were not able to reach native-like competence. This could be due to the parametric differences between the two languages for the grammatical property being investigated.